'Training injury and violence prevention professionals to influence transportation decisions'. (7th October 2012) - Wiliams, A; Porter, J
Abstract : Background: A strong connection exists between transportation decisions and the health of communities. Thus, it is essential for injury and violence prevention (IVP) practitioners to effectively participate in transportation decision-making. In early 2011, the Safe States Alliance conducted a workshop to:  'Make the case' for integrating injury issues in transportation planning;  Understand the process, policies, and players in transportation planning;  Advance safe transportation policies and design within state, regional and local transportation agencies;  Enhance partnerships; and  Increase state and local capacity to promote safety in planning and design. Methods: Prior to the training, attendees were asked to complete homework including a task about transportation planning, a pre-training evaluation, and a 'Personal Action Plan (PAP).' PAPs were to include policies or changes that participants anticipated addressing using injury prevention strategies. Following the training event, participants were given a post-training evaluation and encouraged to update and strengthen their PAPs based on new information obtained from the training. Results: Respondents reported gaining more knowledge of and comfort with every objective they were asked to rate. For example, 94% of participants indicated they felt more 'prepared and comfortable with reaching out to and building new/stronger partnerships with transportation planning and traffic engineering agencies.' Nearly all post-evaluation respondents indicated that they better understood and were more comfortable with all of the topics addressed in the training. Conclusions or Significance: Once equipped with the necessary information, IVP professionals can be empowered to effectively influence transportation decisions at state and local levels.